2016
DOI: 10.1161/jaha.115.002610
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐β Modulates Inflammatory Response in Cerebral Ischemia

Abstract: BackgroundStroke is a leading cause of death in the world. In >80% of strokes, the initial acute phase of ischemic injury is due to the occlusion of a blood vessel resulting in severe focal hypoperfusion, excitotoxicity, and oxidative damage. Interferon‐β (IFNβ), a cytokine with immunomodulatory properties, was approved by the US Food and Drug Administration for the treatment of relapsing‐remitting multiple sclerosis for more than a decade. Its anti‐inflammatory properties and well‐characterized safety profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 52 publications
0
57
0
Order By: Relevance
“…While some studies have found that IFN-I protects against ischemic stroke and can reduce lesion size and leukocyte infiltration into the CNS (In acio et al, 2015;Kuo et al, 2016), others have observed the opposite (Zhang et al, 2017). In line with this latter study, Kavanagh and colleagues have recently demonstrated a causal relationship between IFN-I and microvascular changes including thrombotic microangiopathy in the CNS (Kavanagh et al, 2016).…”
mentioning
confidence: 74%
“…While some studies have found that IFN-I protects against ischemic stroke and can reduce lesion size and leukocyte infiltration into the CNS (In acio et al, 2015;Kuo et al, 2016), others have observed the opposite (Zhang et al, 2017). In line with this latter study, Kavanagh and colleagues have recently demonstrated a causal relationship between IFN-I and microvascular changes including thrombotic microangiopathy in the CNS (Kavanagh et al, 2016).…”
mentioning
confidence: 74%
“…Consistent with these findings, genetic deficiency of CD14, required for microglial production of type I IFNs, results in marked increases in post-MCAO infarct volume [58]. IFNβ modulates inflammatory processes in stroke, in part by suppressing inflammatory cytokine production and reducing microglial activation, resulting in reduced infarct volume and improved neurobehavioral outcomes [92]. Both of these outcomes are important in experimental stroke research.…”
Section: Type I Interferon Signaling In Microglia Modulates Neuroimmumentioning
confidence: 90%
“…IFN‐β significantly helps in obviating neuro‐inflammatory conditions of the central nervous system and improves the pathogenesis of many neurological conditions. A report suggested its role in decreasing neuronal cell death and increasing functional recovery attenuating inflammation after stroke onset (Kuo et al, ).…”
Section: Strokementioning
confidence: 99%
“…Type I IFNs (IFN‐α and IFN‐β) exhibit a wide breadth of biological activities (antiviral, anti‐inflammatory, and anti‐proliferative) (Kuo et al, ). The latter occurs via cytotoxic stimulation of numerous cells of the immune system such as natural killer cells, monocytes, T cells, macrophages, and dendritic cells.…”
Section: Interferonmentioning
confidence: 99%
See 1 more Smart Citation